Clinical Characteristics and Treatment Outcomes of Definitive versus Standard Anti-Tuberculosis Therapy in Patients with Tuberculous Lymphadenitis - Yousang Ko (Journal of Clinical Medicine, 2019)
Although it is necessary to culture Mycobacterium tuberculosis from tuberculous lymphadenitis (TBL) patients for definitive therapy, based on the drug-sensitivity test (DST), substantial cases remain culture-negative. Limited data are available regarding the treatment outcomes after standard anti-tuberculosis therapy in culture-negative TBL. The aim of this study was to compare the recurrence rates between definitive anti-tuberculosis therapy, based on DST and standard anti-tuberculosis therapy in culture-negative TBL. A multicenter retrospective cohort study was performed from 2011 to 2015 in South Korea. The study population was divided into two groups according to treatment type. A total of 234 patients with TBL were analyzed, who were treated with definitive (84 patients) and standard anti-tuberculosis (150 patients) therapy, respectively. During a 28.0 (24.0–43.0) month follow-up period, nine cases (3.8%) had recurrence of TB after treatment completion. The recurrence rate was not significantly different between the two groups (2/84, 2.4% in definitive anti-tuberculosis therapy group versus 7/150, 4.7% in standard anti-tuberculosis therapy group, p = 0.526). The recurrence in all nine cases was diagnosed as clinical recurrence rather than microbiological recurrence. Therefore, culture-negative TBL can be treated with standard anti-TB medication, although DST is not available but clinically stable after initiation of treatment.